Does the Retül System provide reliable kinematics information for cycling analysis? - Ribeiro Branco, G.; De Michelis Mendonça, L.; Alves Resende, R.; Pivetta Carpes, F. (Journal of Science and Cycling, 2022)
The Retül Vantage system is a popular tool to assess dynamic positioning of cyclists. Despite of using a low sampling rate (18 Hz) to record position data, Retül measures shows a moderate to very high correlation with data from gold-standard tridimensional camera systems reaching higher sampling rates, but its reliability has not been tested. Here we assess the reliability of the Retül Vantage system for kinematic assessment of cyclists. This cross-sectional study had two phases. Phase 1 included a survey with certified Retül bike fitters to select the most common variables used in cycling kinematics assessment. Phase 2 involved assessment of the selected cycling kinematics variables to check for intra-examiner reliability. Ten bike fitters answered the online survey (response rate of 47.6%) and 7 variables were identified as the most common to conduct during bike fitting analysis. Then, ten cyclists were submitted to kinematic assessments and Vantage system variables were checked for inter-examiner reliability and standard error of the variables. Good to excellent inter-tester reliability levels were found for all the 7 kinematics variables tested. Standard error of angular variables was lower than 3º for all as well as lower than 5 mm for the linear variable tested. The minimal detectable difference values ranged from 2.15 to 6.55º for angular variables and of 15.51 mm for linear variables. A high and very high degree of intra-rater reliability can be achieved using Retül Vantage system for kinematics assessment of the most common variables included in bike fitting.